Strategic Information Technology and Portfolio Management 2009
DOI: 10.4018/978-1-59904-687-7.ch008
|View full text |Cite
|
Sign up to set email alerts
|

Strategic IT Portfolio Management for Development of Innovative Competences

Abstract: This chapter presents the concept of strategic information technology portfolio management for development of innovation competences in a project-oriented company. It is a specific type of portfolio management, called project portfolio management. The chapter begins with a strategic basis of projectoriented company, links it to the modern portfolio theory and then expands it into the IT project portfolio management (IT PPM). The role of the IT PPM is to ensure that the group of IT projects supports the achieve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Business incubators give significant contribution in developing high-growth innovative businesses which is why many governments are taking necessary steps to include them in their economic agenda. They create employment opportunities, promote different technologies and nurture entrepreneurial drive [1]. Value that is being created this way is perceived worldwide as a mainstay of economic development programs.…”
Section: Introductionmentioning
confidence: 99%
“…Business incubators give significant contribution in developing high-growth innovative businesses which is why many governments are taking necessary steps to include them in their economic agenda. They create employment opportunities, promote different technologies and nurture entrepreneurial drive [1]. Value that is being created this way is perceived worldwide as a mainstay of economic development programs.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, the research conducted by European Commission revealed that some 79% of companies that introduced at least one innovation since 2011 experienced increase of their turnover by more than 25% by 2014 [2]. Therefore, innovation gained a status of a key driver and precondition for competitiveness [3,4], moreover, a key element of modern management and everyday culture.…”
Section: Introductionmentioning
confidence: 99%